Balancing incentives and disincentives for vaccination in a pandemic - Savulescu, J; Pugh, J; Wilkinson, D (Springer Nature, 2021)
We review the possibilities for and ethics of the use incentives and disincentives to increase vaccination uptake. We argue that disincentives (or mandatory vaccination), such as fines, restriction of movement or education and withholding of benefits can be justified depending on four factors: the gravity of the public health emergency, the safety and effectiveness of vaccines, the comparative expected utility of mandatory measures compared to other alternatives, and the proportionality of costs imposed. We provide a decision algorithm for the ethical use of incentives. Incentives face problems of undue inducement and exploitation. We propose a novel Payment Model which would include economic costing of time, pain, risk of adverse events, including death, and compensation. If education, encouragement and facilitation fail to achieve herd immunity quickly enough, payment for vaccination maybe the fairest way to facilitate uptake of vaccination.